УЛУЧШЕНИЕ ЭНЕРГЕТИЧЕСКИХ ХАРАКТЕРИСТИК ПАРАЛЛЕЛЬНОГО РЕЗОНАНСНОГО ИНВЕРТОРА - Афанасьев , А.М. (Інститут електродинаміки НАН України, Київ, 2012)
Based on the anatysis of the known stinctures the new structure of high-frequency transistor generators for induction heating is synthesized. That structure combines the positive properties of methods offorming the output voltage in the resonant circuit. Using a simulation model the electromagnetic processes are investigated and the energyr efficiency of the proposed structure of IGBT resonant inverter is analyzed. References 3. figures 2.